Investigation of Alkaloids in Opium Poppy (Papaver somniferum L.) Varieties and Hybrids - Levent Yazici; Güngör Yılmaz (Journal of Agricultural Sciences, 2021)
This study aimed to investigate the proportions of morphine, thebaine, noscapine, codeine, oripavine and papaverine alkaloids in poppy varieties and hybrids. Nine parents and 36 hybrid lines were used in the trial. The trial was carried out in 2016 and 2017 in four replications according to the Randomized Block Trial Design. According to the average results of the two years, in parent and hybrid combinations, morphine was found to vary between 0.42% and 1.66%, thebaine between 0.01% and 0.53%, noscapine between 0.01% and 0.31%, codeine between 0.03% and 0.17%, oripavine between 0.00% and 0.12% and papaverine between 0.00% and 0.10%. In the study, Ofis NM x Ofis 1, Ofis 1 x TMO T, Ofis 2 x TMO T, Ofis NM x Ofis 1, Ofis NM x TMO T hybrid combinations were identified as superior hybrids compared to the others.